33‐3: Study of Bonding Technology on Flexible Substrate. Issue 1 (May 2016) - Chen, Li‐Qiang; Sun, Tao; Li, Hong; Zeng, Qing‐Hui; Zhou, Wei‐Feng; Kao, Shan‐Chen; Wang, Da‐Wei
Abstract : IC and FPC bonding technology on flexible substrate (PI) using ACF is a key process for flexible display. In this paper, two methods for IC and FPC bonding were compared. The main difference between the two methods is whether PI substrate is laminated with bottom film or not. The results show that PI substrate without bottom film is more suitable for IC and FPC bonding.